A Co-rich chemically complex intermetallic alloy with extraordinary strength-ductility synergy. (May 2023) - Zhao, Y.L.; Xiao, W.C.; Zhao, Z.K.; Li, Q.; Cui, J.; Luan, J.H.; Liu, C.T.; Liaw, P.K.; Yang, T.
Abstract: High-strength ordered intermetallic alloys are always sought-after in sophisticated structural applications. However, their practical applications have long been hindered by the severe grain-boundary embrittlement. Here, we designed a Co-rich chemically complex intermetallic alloy (CCIMA) with the L12 -type ordered structure, which exhibits an ultrahigh tensile strength of ∼1, 611 MPa and a substantial ductility of ∼37%. These exceptional strength-ductility combination outperforms the majority of common Co-rich intermetallic alloys. The multi-addition of Ta, Ti, and V elements is largely responsible for the significantly increased antiphase boundary energy of the L12 superlattice, which accounts for the high strength. This high degree of ductility is attributed to both the increased fracture resistance of grain boundaries brought about by co-segregation-induced order-to-disorder phase transformation, as well as the high work-hardening capability. Graphical abstract: Image, graphical abstract